PERGULATAN IDENTITAS KULTURAL ANTARA FASTFOOD DAN KUDAPAN - Ferdi Arifin (Universitas Muhammadiyah Surakarta, 2017)
This article aims to identify a society’s identity though its culinary aspect. Nowdays,fastfood has been favourite food dominating traditional one. Youth generationpriorities fastfood than traditional food because they regard it more prestigious.Thisphenomenon can not be separated from the uses of Mass media as an important wayto convey foreign product of fastfood as better culinary than local product (kudapan)selling in traditional market. This research uses qualitative methode such as libraryresearch and observation to analyze the phenomena which is happening. The findingof this research implied that cultural identity can be seen in culinary. Cultural identityin culinary is showed by its substance and making process. Thus, the implication ofthis research is to convey the society to love their traditional culinary as a reflex ofcultural identity.